On the Relation of Public Opinion and Religion: Theoretical Considerations - Hidas, Zoltán (Religions, 2023)
Facing the modern expectations about publicity and the high esteem of public opinion, it can be challenging to disclose the sources of these expectations. After sketching the origin of the idea and reality of publicity from the 18th century onward, practical and theoretical concerns about public opinion are discussed alongside the criticism of Walter Lippmann, evoking seminal conceptions of collectivity and of the crowd. It was the German philosopher Ferdinand Tönnies who, from a sociologically informed perspective, systematically analyzed the idea of public opinion. As a stakeholder of religious demands, public opinion is a metaphysical instance. Publicity seems to be socially centered around public intellectuals peculiarly legitimized by scientific knowledge, who have an immense influence on the shape of public opinion through social imagineries (Charles Taylor). The challenge of having a religious relationship with the world has changed due to the public, but self-transcendent need specific responsibilities even in modern circumstances.